Consequences of Violent Conflicts on The Health Sector in Nigeria: A Critical Appraisal - Oluwabamide, Abiodun J. Oluwabamide (Advances in Social Sciences Research Journal, 2014)
Because the consequences of violent conflicts are usually enormous, no nation can encourage them. They range from loss of human lives, destruction of properties. to population displacement. Any time a society experiences violent conflicts, it faces a great challenge, which would in turn create multiple challenges to key institutions and/or sectors within it such as health, security, economy etc. In Nigeria, a country where conflicts are endemic, year in year out, it witnesses one form of violent conflict or the other with serious consequences on human lives. This has increasingly brought more serious emergencies to the health sector, which is indeed, one of the first and/or immediate bearers of the burdens of conflicts in any society. This paper therefore, examines the role of the health sector in managing the consequences of conflicts in Nigeria. It appraises the sector in view of the increasing challenges facing it. It is recommended that the health sector in Nigeria should be practically overhauled with a view to making it ever ready for emergencies of any magnitude.